Mapping nutrition and gender impacts opportunities in potato market segments - Sylvester Okoth Ojwang; Julius Juma Okello; Mwende, Janet; Mendes, Thiago; Ssali, Reuben; Polar, Vivian; Mayanja, Sarah; Lindqvist-Kreuze, Hannele; Campos, Hugo (CGIAR, 2024)
This brief delves into a refined characterization of development impact opportunities in the existing seed product market segments(SPMSs) within the CGIAR potato breeding program, building on the foundational framework established in MIB #1. We leverage G+ tools for gender analysis to better understand gender responsiveness across the nine predefined potato SPMSs. We also examine the nutritional profiles of populations aligned with these SPMSs, striving to improve the description of the development impact opportunities. The recommendations aim to enhance the CGIAR potato breeding program’s responsiveness to nutritional and gender equity, ultimately guiding future efforts toward more inclusive and effective breeding systems that align with the dynamic needs of the SPMSs.